Delayed neurologic deterioration in the patient with spinal trauma: role of MR imaging. - Silberstein, M; Tress, B M; Hennessy, O (American Journal of Neuroradiology, 1992)
PURPOSE To 1) correlate spinal MR features and modes of clinical presentation associated with symptomatic neurologic deterioration following longstanding spinal trauma; 2) correlate degree of neurologic deficit with spinal MR appearance in these patients; and 3) determine the relationship between new symptoms and ongoing cord compression.METHODS Retrospective examination of MR images, and correlation with clinical data, in 94 consecutive patients.RESULTS Sixty-seven patients presented with either an increase in degree of myelopathy or ascending neurologic level. Spinal cord atrophy (43%), syrinx (41%), and cord compression (24%) were found most frequently. Whereas in patients with complete motor and sensory deficit cord atrophy was the most frequent finding (52%), 75% of patients with useful motor function had normal spinal cords. There was a significant association (P less than .05) between cord compression and the MR findings of cord atrophy and myelomalacia, whereas a normal cord was over twice as frequent in patients without spinal cord compression. MR imaging led to an active change in management in 15% of patients, with improvement following surgery in all operated cases.CONCLUSION Although syrinx is a frequent, and treatable cause of delayed neurologic deterioration, MR will frequently show other abnormalities such as ongoing cord compression. MR imaging should be performed urgently in all patients with new symptoms to enable early treatment to prevent irreversible loss of function.